The Role of Vitamin Deficiency in Liver Disease: To Supplement or Not Supplement? - Anna Licata (MDPI AG, 2021)
Over the past few years, growing interest has been shown for the impact of dietary requirements and nutritional factors on chronic diseases. As a result, nutritional programs have been reinforced by public health policies. The precise role of micronutrients in chronic liver disease is currently receiving particular attention since abnormalities in vitamin levels are often detected. At present, treatment programs are focused on correcting vitamin deficiencies, which are frequently correlated to higher rates of comorbidities with poor outcomes. The literature reviewed here indicates that liver diseases are often related to vitamin disorders, due to both liver impairment and abnormal intake. More specific knowledge about the role of vitamins in liver disease is currently emerging from various results and recent evidence. The most significant benefits in this area may be observed when improved vitamin intake is combined with a pharmacological treatment that may also affect the progression of the liver disease, especially in the case of liver tumors. However, further studies are needed.